The Utilization of Lamtoro Plants as Animal Feed and Means of Reforestation in the Mecerit River, West Pengadangan Village, Pringgasela District, West Nusa Tenggara - Muhammad Omar Al; Tika Wati; Suci Yulia Wulandari; Uyun Fitria Aryanti; Rangga Bayu Asmara; M. Sugandi Ardiansyah; Ikhlas Amalulsyah; Mudrika Lutfiah; Annisa Hijratullah; Nurul Istiqomah; Syahrul (Yayasan Siti Widhatul Faeha, 2026)
The fluctuating availability of feed forage, especially in the dry season, is the main obstacle in the people-scale ruminant livestock business. This service activity aims to optimize the availability of feed through socialization and planting lamtoro (Leucaena leucocephala) as a source of protein forage. The activity was carried out in West Pengadangan Village, Pringgasela District, East Lombok Regency, with a community empowerment approach. The implementation method includes coordination with the village government and breeder partners, socialization through lectures and discussions, technical demonstrations of simple seedlings and cultivation, planting lamtoro seedlings at the agreed planting point, as well as initial monitoring of growth and participant feedback. The results of the activity showed an increase in participants' understanding of the benefits of lamtoro as an additional feed, planting techniques and initial maintenance, as well as the formation of residents' commitment to utilize yard land and less productive land as a source of forage. Planting seedlings is the first step in establishing a sustainable source of feed which is expected to reduce dependence on finding food from outside the village in critical periods. This activity suggests follow-up in the form of maintenance assistance, strengthening the availability of seeds, and expanding the planting area through livestock groups.